The wonder and importance of biological control in farming and agrifood systems - Wyckhuys, Kris A.G. (International Food Policy Research Institute, 2024)
Simplemente agotado … how tired!! Sunburned, running low on water and my trousers caked with mud—that’s how my first day of field research in the Yeguare River valley, Honduras, ended back in 2002. From that day on, for two years, I imagined myself aboard Darwin’s Beagle or the Victoria, the carrack on which Magellan had circumnavigated the globe. On my daily journey of ecological discovery and exploration, I was alone yet more connected than ever. Magnifying glass in hand and aspirator bottle at the ready, my days were spent scanning maize plants’ foliage for the six-legged creatures that devoured farmers’ crop pests. Those bugs kept me going: I was hooked on the mystery, surprise, and beauty of a seemingly simple, yet utterly complex farmland ecosystem. To cite the late E.O. Wilson, I could have spent “a lifetime in a Magellanic voyage” around those maize stalks! Filled with a sense of wonder, every day brought a revelation, a new interaction logged, and a piece of the food system sustainability puzzle uncovered. Most of my days ended tired … yet truly inspired.